ENVIRONMENTAL CORRELATES OF SUICIDE - ASOGWA, EMMANUEL U (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
Suicide is a serious global public health problem, which claims a life in every thirty seconds, 3000 lives daily, and over one million lives yearly, with up to ten to twenty million people attempting suicide every year. It is the tenth leading cause of death in the world, and the second among the youth, following accident. And it has increased up to sixty-five percent in recent years, especially in developing countries. It has become increasingly apparent that suicide in the “21st" century has gone beyond being the traditionally 'socio-psychiatric phenomenon, but a multifaceted and multifactorial health problem with environmental influences. Literature shows that environment may induce or perpetuate or aggravate suicide potential, hence the need to identify environmental correlates of suicide, and suggest the roles or relevance of environmental. health in the prevention and management of suicide issues in the society.